Development Model of Gender Equality Study in Inheritance Distribution of Tanah Luwu Communities - Andi Sukmawati Assaad; Baso Hasyim; Abdul Manan Ismail; Amiruddin Kuba (Jurnal Hukum dan Peradilan, 2023)
This research’s aims are 1. analyze the Tanah Luwu people's inheritance distribution, 2. analyze the views of Gender Equality on how to distribute the inheritance of the Tanah Luwu Tribe community, 3. analyze the model for developing gender equality in the inheritance distribution system of the Tanah Luwu people. This study uses an explorative-qualitative research method that describes the development model of gender equality studies in the distribution of inheritance for the people of Tanah Luwu by studying inheritance cases enforced concerning parts and kinship systems. The study shows that the people of the Tanah Luwu tribe generally adhere to Islam; however, they still highly respect the customs passed down from generation to generation to their families, including in inheritance. Therefore, when asked about the inheritance laws that apply, they answer Islamic inheritance laws. However, they use inheritance laws according to their wishes or the appointing system and consider it fair. Gender equality views the inheritance distribution of the people of Tanah Luwu as unfair; thus, there is concern among the heirs. Tension can lead to conflicts or disputes. The gender equality development model is the conflict management and conflict transformation approach.